IMPLEMENTASI PERSONAL HYGIENE ROOM ATTENDANT PADA HOUSEKEEPING DEPARTMENT SELAMA MASA PANDEMI COVID-19 DI HARRIS RESORT BARELANG BATAM - Devid Simatupang; Theresa Panggabean (JURNAL MEKAR, 2022)
This study aims to determine the personal hygiene of the room attendant and how the room attendant implements personal hygiene during the covid-19 pandemic. From this study the authors got the results from the formulation of the first problem that the knowledge of the room attendants was still a little limited, because they did not understand in explaining personal hygiene. Lack of willingness and initiative from room attendants to understand personal hygiene knowledge itself. Meanwhile, related to body image, the room attendant was quite good at understanding and implementing it. From the second formulation problem that the implementation of personal hygiene in room attendant officers is quite good after the author conducted interviews with several informants because there was still attention from superiors and checking during briefings before starting operations or while operational.